2022
DOI: 10.1186/s12865-022-00519-y
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of immunological responses by aqueous extract of Datura stramonium L. seeds on cyclophosphamide-induced immunosuppression in Wistar rats

Abstract: Background Datura stramonium L. (Solanaceae) is used traditionally in west Africa to treat asthma, epilepsy, rheumatoid arthritis, filariasis microbial infections and conjunctivitis. This study investigated the immunomodulatory effects of aqueous seed extract of D. stramonium L. (ASEDS) on Wistar rats. Methods Thirty Wistar albino rats (180–200 g) were randomized into 6 groups (n = 5). Group 1 received distilled water only. Rats in groups 2–6 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 80 publications
(86 reference statements)
2
2
0
Order By: Relevance
“…Previous studies have shown that α-terpineol alleviates asthma in mice by reducing EOS and balancing Th1/Th2 cytokines. 31–33 In this study, we also found that α-terpineol decreased the production of the Th2-type cytokines IL-4, IL-5 and IL-13. 26,32,34 The molecular mechanism by which α-terpineol exerts protective effects against asthma was analysed using UPLC/MS-MS techniques.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Previous studies have shown that α-terpineol alleviates asthma in mice by reducing EOS and balancing Th1/Th2 cytokines. 31–33 In this study, we also found that α-terpineol decreased the production of the Th2-type cytokines IL-4, IL-5 and IL-13. 26,32,34 The molecular mechanism by which α-terpineol exerts protective effects against asthma was analysed using UPLC/MS-MS techniques.…”
Section: Discussionsupporting
confidence: 65%
“…Previous studies have shown that α-terpineol alleviates asthma in mice by reducing EOS and balancing Th1/Th2 cytokines. [31][32][33] In this study, we also found that α-terpineol decreased the production of the Th2-type cytokines IL-4, IL-5…”
Section: Discussionsupporting
confidence: 65%
“…This inhibitory effect is dieted by reduced the adenosine elevated levels through restoration of T-cell homeostasis [ 125 128 ], regulation of Th17 cell differentiation [ 129 ], regulation of Th17/Treg-related cytokine levels, reduction of autoantibody production, and regulation of nucleoside triphosphate diphosphohydrolase (NTPDase) activities [ 128 , 130 ]. Collectively, QUE established the immune-regulatory effect and is considered one of the most important natural candidates that can used for RA therapy [ 131 , 132 ] as mentioned in Fig. 11 .…”
Section: Natural Productmentioning
confidence: 99%
“…Pathological examination showed arthritic cell infiltration and cartilage erosion in the model group, and a slight relief of joint lesions was observed in the CGA group. Therefore, CGA is also gradually being used to treat RA ( Joshua et al, 2022 ; Lee et al, 2018 ). Lee et al examined the effect of CGA on septic arthritis caused by Candida albicans and found a significant reduction in edema ( Lee et al, 2008 ).…”
Section: Chlorogenic Acid In Clinical Applicationsmentioning
confidence: 99%